Critical Conditions for the Ignition of a Gel Fuel under Different Heating Schemes - Olga Gaidukova (MDPI AG, 2021)
A model was developed to research the critical conditions and time characteristics of the ignition of gel fuels in the course of conductive, convective, radiant and mixed heat transfer. MATLAB was used for numerical modeling. Original MATLAB code was established pursuant to the developed mathematical model. For gel fuel ignition at initial temperatures corresponding to cryogenic storage conditions with different heating schemes, a numerical analysis of interconnected processes of heat and mass transfer in the chemical reaction conditions and exothermic and endothermic phase transitions was conducted. The model was tested by comparing the theoretical results with the experimental data. Dependencies were established between the key process characteristic (i.e., the ignition delay time) and the ambient temperature when the following parameters were varied: emissivity, heat emission coefficient, activation energy and pre-exponential factor of the fuel vapor oxidation reaction. The critical values of the main parameters of the energy source were determined. For these values, gel fuel ignition conditions were consistently realized for each heating scheme. The critical heat fluxes necessary and sufficient for the ignition of typical gel fuels were determined.